Successful Treatment of Toxic Epidermal Necrolysis More Than 70% Body Surface Area Involved with Imunosuppressive Therapy and Amniotic Membrane Craft in Cornea - Uddin, Md. Rokon; Bhuiyan, Motahar Hossain; Akhter, Farjana; Baker, Md. Abu; Akramuzzaman, AKM (Medicine Today, 2012)
Medicine Today 2009 Volume 21 Number 02 Page 74-76 DOI: http://dx.doi.org/10.3329/medtoday.v21i2.12552